Scrutinizing Generation Z's Interpretation of Social Justice: A Case Study in Khomeinishahr, Iran - Akbar Zareshahabadi; Alireza Asgari; Reza Javadian (جامعه شناسی کاربردی)
Introduction Social justice refers to the equitable distribution of societal resources among all individuals, emphasizing fairness and equality across social, economic, and political domains. This concept focuses on the mechanisms by which societies allocate resources, including material goods, as well as social benefits, rights, and protections (Chapin, 2017). Nadiry and Shakoori (2011) highlight that generational differences significantly influence perceptions of social justice, overshadowing factors, such as gender, class, and education. An Ipsos survey conducted across 29 countries reveals that young people are more likely than previous generations to view inequality as a pressing issue in their nations. They also perceive their gender as one of the most discriminated groups today. Moreover, the belief that personal success relies on merit and effort is more prevalent among older generations, whereas Generation Z exhibits the least faith in this notion. This generation places a heightened focus on discrimination against women compared to earlier cohorts (Taylor, 2024). The present study examined Generation Z's experiences with social justice, explored their interpretation of the concept, and investigated their proposed solutions for achieving social justice on a societal level.